Radiogenic Vaginal Angiosarcoma: a Clinical Case - K. V. Menshikov; A. V. Pushkarev; A. V. Sultanbaev; V. A. Pushkarev; I. A. Sharifgaliev (Креативная хирургия и онкология)
Background. Vaginal sarcomas are rare malignant mesenchymal neoplasms. Incidence rate of vulvar and vaginal sarcomas ranges from 1 to 3%. Vaginal sarcomas are usually represented by leiomyosarcomas in reproductive-age women. More seldom are soft tissue fibrosarcomas, angiosarcomas, malignant fi brous histiocytomas and alveolar soft tissue sarcomas. Tumours induced by prior radiation therapy deserve special concern. In oncogynaecology, radiation therapy is commonly applied in cervical and endometrial cancer therapy. According to some evidence, average development time of a secondary tumour after completion of radiation therapy is 10.8 years. The relative risk of vaginal cancer increases by a factor of 300 after radiation therapy.Materials and methods. The reported clinical case represents a rare vaginal tumour, angiosarcoma, developed 26 years after radiation therapy for gynaecological cancer.Results and discussion. A 78 years-old patient underwent combined tumourectomy of the posterior vaginal wall with resection of the anterior rectal wall and application of preventive transversostoma. No postoperative complications were observed.Conclusion. Surgical treatment is a method of choice with patients of such kind and allows local containment of the disease.